Olive, again - Strout, Elizabeth (New York : Random House, 2019)
"Funny, wicked and remorseful, Mrs. Kitteridge is a compelling life force, a red blooded original. When she's not onstage, we look forward to her return..."* And now, indeed, Olive Kitteridge has returned, as indomitable as ever. "It turns out--I just wasn't done with Olive," said Strout. "It was like she kept poking me in the ribs, so I finally said 'Okay, okay...'" Now Olive returns, this time as a person getting older, navigating her next decade as she comes to terms with the changes--sometimes welcome, sometimes not--in her own life. Here is Olive, strangely content in her second marriage, still in an evolving relationship with her son and his family, encountering a cast of memorable characters in the seaside town of Crosby, Maine. Whether it's a young girl coming to terms with the loss of her father, a young woman about to give birth at a baby shower, or a nurse who confesses a secret high school crush, the irascible Olive improbably touches the lives of others. Elizabeth Strout has achieved greatness by brilliantly laying bare the inner lives of ordinary people, by focusing on the small moments of connection which can dislodge lifelong grief and longing, and unite her characters through moments of transcendent grace. Olive, Again is another lasting work of fiction by this remarkable writer, and a cause for celebration among readers everywhere.
HB